Atypical mycobacteria in a superficial femoral artery occlusion. (10th March 2011) - Determann, C; Hill, AT; Monaghan, H; Fraser, SCA
Abstract : There is indirect evidence that atherosclerosis may occur in association with bacterial infection. The authors report the case of a young woman who presented with right calf claudication caused by a short occlusion of the superficial femoral artery. Histological examination of the excised segment of artery revealed atheroma and atypical mycobacteria within adventitial caseating granulomata. The possible causes are discussed.